Akun Pembelajaran: The Implementation by English Teachers in Teaching Process - Agustin Is Saidi; Moon Hidayati Otoluwa; Adriansyah Abu Katili (Ideas Publishing, 2022)
Due to the importance of technology in pandemic, Indonesias government had prepared education using technology by cooperating with Google to make Akun Pembelajaran to accesses online learning media for teachers and students. However, since the regulation number 23 in 2021 was released and other regions used Akun Pembelajaran, government of Boalemo regency implemented the regulation after 4 months. Additionally, the purpose of this research was to investigate the implementation of Akun Pembelajaran by English teachers in Botumoito junior high schools. There were six schools taken at this research, those were SMPN 1, SMPN 2, SMPN 3, SMPN 4, SMPN 5 and SMPN 6. This research used case study as the method of research. This research focuses on phenomena (Akun Pembelajaran) that are real in Botumoito sub-district junior high schools. This research also used qualitative research as the approach of research and unstructured-interview as the technique of collecting the data. Based on the results of the research, it was found that all the teachers in Botumoito had not implemented Akun Pembelajaran optimally. The implementation was on the subject of storing the data, calculating the students scores, accessing Canva for education, and collecting teaching materials. It was implicated that there was barely facilitation which support the teachers in getting information and practically train the teachers on how to implement Akun Pembelajaran. Therefore, a further training on how to implement Akun Pembelajaran is wisely expected. Adapun mengingat pentingnya teknologi di masa pandemic, pemerintah Indonesia telah menyiapkan pendidikan menggunakan teknologi dengan menggandeng Google untuk membuat Akun Pembelajaran guna mengakses media pembelajaran daring bagi guru dan siswa. Namun, sejak perpres 23 Tahun 2021 dirilis dan daerah lain menggunakan Akun Pembelajaran, pemkab Boalemo baru mengimplementasikannya selama 4 bulan. tujuan dari penelitian ini adalah untuk mengetahui penerapan Akun Pembelajaran oleh guru di SMP Botumoito. Terdapat enam sekolah yang diambil dalam penelitian ini, yaitu SMPN 1, SMPN 2, SMPN 3, SMPN 4, SMPN 5 dan SMPN 6. Penelitian ini menggunakan penelitian studi kasus sebagai metode penelitian. Penelitian ini juga menggunakan pendekatan kualitatif dan wawancara tidak terstruktur sebagai teknik pengumpulan data. Berdasarkan hasil penelitian diketahui bahwa semua guru di Botumoito belum mengimplementasikan Akun Pembelajaran secara optimal. Implementasinya pada pokok menyimpan data, menghitung nilai siswa, mengakses Canva untuk pendidik, dan mengumpulkan bahan ajar. Hal ini berimplikasi pada minimnya fasilitasi yang mendukung guru dalam mendapatkan informasi dan secara praktis melatih guru dalam mengimplementasikan Akun Pembelajaran. Oleh karena itu, pelatihan lebih lanjut tentang bagaimana mengimplementasikan Akun Pembelajaran secara bijaksana diharapan.